The impact of intellectual property right regimes on self employed entrepreneurship: an international analysis - Burke, Andrew; Fraser, Stuart (Cranfield University School of Management, 2007)
The importance of IPR regimes for large firm innovation is well documented but less is known about their impact on self-employed entrepreneurship which is typically less innovative. The paper sets out to estimate the net effect of the various elements that comprise an IPR regime including the political system, the laws, and institutions as well as a general familiarity with and respect for IPR related products. Cumulatively, the analysis indicates that a well developed IPR regime has a net positive effect on the selfemployment activity. Since the self-employed sector is possibly the only segment of the enterprise base where IPRs may be expected to have a negative effect it provides a useful contribution to our empirical understanding of the welfare effects of IPRs on the entrepreneurial economy and economic development more widely. Contrary to some of the most vocal objections to the TRIPS Agreement we find that rather than undermine the self-employed enterprise base it actually boosts it. We find that half-hearted IPR conventions, in this case the Phonograms Convention, designed to accommodate countries with a weak desire to support IPRS undermines this positive effect. We do not find any evidence to suggest that the organizations which tend to be associated with the enforcement of IPR laws such as Interpol, ISO, PCA, UNCTAD, UNESCO, WIPO and the WTO had any effect over and above WIPO and the WTO helping to create TRIPS in the first place. The evidence in the paper indicates that the standard practice of international economic development aid where recipient countries have been encouraged to embrace democracy and IPRs (in particular, the TRIPS Agreement) seems to have been prudent. Most likely these initiatives would act to boost the self-employed enterprise base in developing and transition economies.
Keywords: Self-employment; Intellectual property rights; Law